Rudolf Haym (1821-1901) i jego zielonogórskie korzenie = Rudolf Haym's Zielona Góra roots - Janczys, Anna; Mróz, Tomasz (1975- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents a biography and major works by German philosopher R. Haym (1821-1901) - who has hitherto caught little interest of Polish historians and philosophers - and draws on those passages in his autobiography (Aus Meinem Leben. Errinerungen, Berlin 1902) which describe his youth spent in Zielona Góra. Since his father was a headmaster, his family home was in the headmaster's flat in the school building.
Keywords: Haym, Rudolf (1821-1901); biografia; filozofia niemiecka; 19 w.